(untitled) (Journal of the College of Basic Education, 2026)
Because the Holy Quran is distinguished by the eloquence of its expression, the precision of its words, and their beauty, Scholars have been amazed by it it and gathered around it to study these words. from their various aspects (linguistic, grammatical and samantic) Based on this, I have chosen to study two words from the wise Reminder, the words (face, and faces) as these two words occupy multiple grammatical positions and carry different meanings in the contexts in which they appear, This research was undertaken to identify those locations and reveal those indications, This research was based on two sections, the first of which dealt with the word (face) and the second dealt with the word (faces). I have benefited from numerous sources and references, induding book on language and grammar, as well as Linguistie dictionaries.